Pengaruh Indroduksi Peralatan Produksi Terhadap Perkembangan Kerajinan Cukli - M. Wijana; I Wayan Joniarta; A.A Alit Triadi (Jurusan Teknik Mesin FT Universitas Mataram, 2022)
The demand for cukli crafts in lendang ree village continues to increase. To improve the quality and quantity of cukli crafts, it is necessary to carry out various innovations to empower the artisan community. Problem faced by cukli craftsmen in improving their quality and productivity, including the limitations of production equipment. With the existence of a free market in the coming years and the tight business competition, it must be anticipated immediately. Usaha coaching to help craftsmen is to provide assistance in the form of equipment. To streamline coaching activities, training and mentoring are carried out as well as evaluations to see the development of the assistance that has been provided. . This program has been running well, the introduction of equipment, training and mentoring has gone well. The quality of products and the productivity of craftsmen are increasing, craftsmen are growing, income is increasing. The craftsmen are very happy, enthusiastic and very excited to receive this program. so that training and mentoring can run quickly and can have an impact on the development of cukli craftsmen.